"IMPROVEMENT OF THE METHOD OF RADIATION DIAGNOSTICS OF DEGENERATIVE CENTRAL STENOSIS OF THE CERVICAL SPINAL CANAL" (American Journal of Interdisciplinary Research and Development, 2022)
Data on the prevalence of symptomatic degenerative lumbar stenosis are very contradictory, and information about the clinical characteristics of its morphological subtypes (features of pain syndrome, functional and neurological deficits, and the degree of decline in quality of life) is not sufficiently studied.